The Relationship between Knowledge and Motivation of Posyandu Cadres in Improving the Quality of Stunting Toddlers in Sumbersari Village, Lowokwaru District, Malang City - Indriana Alfiyah; Mika Vernicia (Journal of Hospital Management and Services, 2019)
The result of a preliminary study in Sumbersari Village Malang, can be seen from the problems that occur there are still many cadres who do not understand about stunting and less of motivation from the result interview conducted with 15 Posyandu Cadre’s obtained a good percentage (14%), medium (46%), and low (40%). Objective: The objective of the study is to investigate the correlation between knowledge and cadre‟s motivation in improving the quality of life stunting toddlers in Sumbersari Village, Malang Method: The study employed analytical correlation with cross sectional design. The study was conducted on July 20 2017. The population of the study was 67 Posyandu cadres with a sample of 64 cadre’s . probability sampling was used as sampling technique with the Simple Random Sampling technique. The data were collected through questionnaire. The data were analyzed by using Spearman Rank correlation. Result: The result showed that cadres with enough knowledge were 31 people (48,4%), and 29 people have less motivation (45,3%). The result of statistical test of the knowledge obtained significant p–value =0.006<0.05 with a Spearman Rank correlation value of 0.338 (positive correlation). Conclusion and Suggestion: There was a correlation between knowledge and motivation of posyandu cadres in improving the quality of life for stunting toddlers in Sumbersari Village. It is expected that cadres increase their knowledge and motivation by having willing and support to learn deeper to get a better result.